Regional variation of pediatric inflammatory bowel disease in Saudi Arabia: Results from a multicenter study - Mouzan, Mohammad I El; AlEdreesi, Mohammed H; Hasosah, Mohammed Y; Al-Hussaini, Abdulrahman A; Sarkhy, Ahmad A Al; Assiri, Asaad A (World journal of gastroenterology : WJG, 2020)
Incidence and severity variations of inflammatory bowel disease (IBD) have been reported from Western populations between continents and regions of the same countries. However, no data were available from other countries. To investigate the regional differences in the IBD profiles of pediatric patients from the Kingdom of Saudi Arabia. Data from a national multicenter IBD study were used. The incidence, time trend, and clinical presentation of Crohn's disease (CD) and ulcerative colitis (UC) in the Central region (CR), Western region (WR), and Eastern region (ER) were analyzed and compared. Statistical analysis included Poisson regression analysis for incidence variation and Chi-square test for demographic and clinical parameters. A < 0.05 was considered significant. The prevalence of positive family history was lower in children with CD from the ER than the CR or the WR. Consanguinity rate was higher in children with CD and UC from the CR and the ER, respectively. The incidences and time trends of CD and UC were not significantly different between regions. In the ER, a significantly higher percentage of children with CD presented with abdominal pain ( < 0.001), blood in stools ( = 0.048), stricturing or penetrating disease ( = 0.029), higher erythrocyte sedimentation rate ( < 0.001), higher C-reactive protein ( < 0.001), higher anemia ( = 0.017), and lower albumin level ( = 0.014). For children with UC from the ER, a significantly higher percentage presented with anemia ( = 0.006) and a lower percentage with pancolitis ( < 0.001). The most important finding is the identification of significantly more severe presentation of CD in the ER of the Kingdom of Saudi Arabia. Prospective studies are needed to explain such variations.